Penerapan Metode Problem Solving Dalam Mengembangkan Analytical Skills Peserta Didik Pada Mata Pelajaran Pendidikan Agama Islam Dan Budi Pekerti Kelas XI SMAN 1 Simpang Teritip - Afuleno, Aldo; Janawi, Janawi; Rudini, Rudini (LENTERNAL: Learning and Teaching Journal, 2024)
This research is motivated by the lack of analytical skills which trigger low student learning outcomes. The aim of this research is to find out whether there is an application of the Problem Solving Method in developing students' Analytical Skills in the subjects of Islamic Religious Education and Character in class XI, majoring in Science. This research was conducted at SMAN 1 Simpang Teritip using the Problem Solving method. The method used in this research uses quantitative methods. The type of research used was quasi-experimental, using a nonequivalent control group design. Data collection for this research used 20 pre-test and post-test multiple choice questions, while the data analysis technique used the t-test with the paired samples test formula, and the Smirnof t-test 2 colmogrof test with the independent samples test formula. This research concludes that based on the calculations that have been carried out on the test result data, it is found that the application of the Problem Solving method has an influence in improving and developing analytical skills in PAI and Moral Education subjects. Proved by hypothesis testing using the Smirnof colmogroph test for 2 samples with the independent samples test formula, it was obtained that tcount was 9,473 ttable 1,681, then tcount > ttable, namely 9,473 > 1,681 and the sig > α value, namely 0.000 < 0.05, so H0 was rejected and Ha was accepted. With a significance level of α 5% (0.05). So there is a significant difference after using the Problem Solving method compared to conventional strategies.